ANALISIS PENETAPAN HARGA DALAM JUAL BELI SEPEDA BEKAS DI BENGKEL MA’HAD AL-ZAYTUN PERSPEKTIF HUKUM EKONOMI SYARIAH - Fitri Annisa, Wina; Maulana, Rizal; Prawoto, Imam (Cahaya Ilmu Bangsa, 2024)
There are two main problems of this research, namely pricing in the sale and purchase of used bicycles at the Ma'had Al-Zaytun workshop and the application in the perspective of Sharia Economic Law. This research is motivated by the need to examine whether the process of pricing used bicycles has met the criteria stipulated in sharia economic law, as well as how the pricing policy in the workshop is in line with the values of honesty, willingness and justice in sharia economic law. This research aims to analyze the process of pricing used bicycles at Ma'bad Al-Zaytun Workshop and assess its suitability with the principles in sharia economic law. This research uses a descriptive qualitative method with data collection techniques through interviews, observation, and documentation to understand the pricing practices at the workshop. The results show that the pricing of used bicycles at the Ma'had Al-Zaytun Workshop is influenced by the condition of the bicycle, repair costs, and scarcity factors. This pricing also applies the principles of fairness and transparency in accordance with sharia economic law. By offering quality used bicycles and affordable prices, transactions take place without elements of maisir, gharar, riba, and batil. Both parties benefit and the transaction is carried out on a consensual basis, reflecting social and religious values that support the creation of trust and customer satisfaction. This research is expected to be a guide for Ma'had Al-Zaytun workshops in setting fair and Shari'a-compliant prices, as well as contributing to the Islamic economic literature in the context of buying and selling used goods. Keywords: Pricing, Used Bicycle Sale and Purchase, Sharia Economic Law